Manajemen Pembelajaran Mapel Rumpun PAI Berbasis Scientific Approach di MIN Se-Eks Karasidenan Pekalongan - Mustakim, Zaenal (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aims to explore the management of PAI learning based on a scientific approach applied in some Madrasah Ibtidaiyah Negeri of Pekalongan residency, the constraints experienced by the teachers in implementing PAI subjects based on scientific approach, and students' responses after having the learning process of PAI based on scientific approach. This study belongs to descriptive qualitative research and uses field research. The data collection was done through interview, observation and documentation. The result shows: (1) the implementation of PAI learning has been conducted well, full of motivation, creative, innovative, systematic, and in accordance with the steps of learning using the formula of 5M. (2) there are three obstacles faced by the teachers in implementing PAI learning based on scientific approach, namely the students’ ability, the teachers’ competence, and the availability of learning facilities. (3) the response shown by the students after experiencing the learning process of the PAI based on scientific approach is that they become more active, communicative, critical, and enthusiastic in the learning process and show high curiosity